DISTURB SLEEP IS A PATHOLOGICAL CONDITION THAT DISRUPTED THE HEALTH-AN AYURVEDIC APPROACH WITH CONTEMPORARY VIEW (AYUSHDHARA, 2016)
Sleep is thought to have powerful restoratives properties. Sleep deprivation in human is widely believe to impact in health system, and is a well known risk factor for development of many diseases. All most all individual suffer from disturb sleep at least one occasion in his life time. Ayurveda describe sleep (Nidra) as a basic need like food and copulation. It is inevitable of all living being like death. Anidra (Disturb sleep) include any kind of abnormal sleep in respect of amount and quality in classical text of Ayurveda. Anidra has been described under the heading of causative factor, premonitory symptom, clinical feature, complication and bad prognostic sign of many diseases and as a disease itself in classical texts. Contemporary science also regarded disturb sleep is one of the pathological condition that distorted homeostasis. All major physiological systems affected by it. Disturb sleep alter the neurological, behavioral, metabolic as well as immune response. The circadian clock controls most hormone secretion and sleep has a major impact on it. Disturb sleep hampered the metabolism of many hormone and there secretions also. Sound sleep is a major criterion for maintenance of normal health. This review is try to illustrate how disturb sleep affect the health and its acute as well as chronic consequences.